A solid iron salt catalyst for selective conversion of biomass-derived C5 sugars to furfural. (15th September 2021) - Sun, Kai; Shao, Yuewen; Liu, Peng; Zhang, Lijun; Gao, Guoming; Dong, Dehua; Zhang, Shu; Hu, Guangzhi; Xu, Leilei; Hu, Xun
Graphical abstract: Highlights: FeClx was successfully grafted on D008 (acidic resin) via an ion-exchange method. Modification of D008 with FeClx generated new Lewis acid sites. Synergistic effect of Brønsted and Lewis acid site facilitated furfural production. 96.3% yield of furfural was obtained from xylose conversion over FeClx/1 -D008. FeClx presence suppressed polymerization via enhancing the activation energy. Abstract: Salt is widely applied as catalyst but it is difficult to separate the soluble salt from the reaction medium. To solve this issue, in this study, a solid salt catalyst (FeClx -D008) was prepared by using a solid acidic resin (D008) and FeCl3 via a partial ion exchange method as the demonstration of proof of concept. The introduction of FeCl3 onto D008 replaced some Brønsted acid sites with newly generated Lewis acid sites. The synergistic effect of the Brønsted and Lewis acidic sites rendered the catalyst with excellent catalytic selectivity for the production of furfural from C5 sugars (highest yield: 96.3%). The kinetic study showed that the introduction of FeClx onto D008 enhanced the activation energy (AE) from xylose to polymer while lowered the AE from xylose to furfural. The FeClx species could strongly coordinate with the -SO3 − group in D008 with the high resistivity to leaching. The successful immobilization of FeClx species on D008 solved the issue for separation of soluble salts from the reaction medium, which is also an attempt for application of resin-based solid salt as the catalyst in acid-catalyzed reactions.